Le Chaos et la Nuit di Henry de Montherlant e il tramonto dell’eroe solare - Marilena, Genovese (IJRDO - Journal of Social Science and Humanities Research, 2019)
The purpose of this paper is to examine <em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Henry de <em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Montherlant’s <em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">novel <em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Le Chaos <em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">et la <em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Nuit<em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;"> (1963). The focus will be on the main character, Celestino Marcilla, an exiled Spanish anarchist, obsessed by the Civil War. We will demonstrate like his paranoia and his fear of death are an antithesis of the joys and the heroism expressed by Alban de Bricoul, the main character of the early literary works, Le Songe and Les Bestiaires. According to the <em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">pessimism of the last years – the author had been blind in the left eye and had been sick in 1969 and 1971 – this novel <em style="background-color: transparent; color: #000000; cursor: text; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; outline-color: transparent; outline-style: none; outline-width: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">can be considered the sadly final of the art of Henry de Montherlant.